Preparation method of composite modified charcoal soil conditioner

By combining biochar with nanomaterials and mixing them with natural polymers, a composite modified biochar soil conditioner was prepared, which solved the problems of low efficiency and high cost of existing soil repair methods, and achieved efficient removal of heavy metals and improved soil environment.

CN119685028APending Publication Date: 2025-03-25济宁市农业技术推广中心
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411850447.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Existing soil repair methods are difficult to achieve efficient, economical and environmentally friendly heavy metal pollution restoration effects. Traditional methods have problems such as large engineering volume, high cost, long cycle, poor results or may aggravate soil degradation.

Method used

Using the preparation method of composite modified biochar soil conditioning agent, biochar is prepared by carbonizing crop waste and combined with nanomaterials (such as nano zero-valent iron or nanotitanium oxide), the nanomaterials are uniformly dispersed by ultrasonic treatment, and then mixed with natural polymers and dried and crushed to prepare a composite conditioning agent with efficient removal of heavy metals.

Benefits of technology

Through the physical adsorption of biochar and the chemical reaction of nanomaterials, the removal efficiency of heavy metals is significantly improved, the stability and applicability of the conditioner is enhanced, the pH value, organic matter content and moisture retention ability of the soil are improved, the growth of plants is promoted and the bioavailability of heavy metals is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005190434910000101
    Figure BDA0005190434910000101
  • Figure BDA0005190434910000111
    Figure BDA0005190434910000111
  • Figure BDA0005190434910000112
    Figure BDA0005190434910000112
Patent Text Reader

Abstract

The invention discloses a preparation method of a composite modified charcoal soil conditioner, which comprises the following steps: S1, selecting crop wastes, cleaning, and removing impurities; the cleaned waste is carbonized at the temperature of about 300-600 DEG C under the anoxic condition, and biochar is obtained; s2, after carbonization is completed, cooling and crushing the biochar; s3, preparing a nano material; s4, weighing pre-prepared charcoal and a nano material according to a ratio of 3: 1; s5, putting the biochar and the nano material into an ultrasonic cleaning machine, adding a proper amount of deionized water, and carrying out ultrasonic treatment; s6, after ultrasonic treatment, transferring the mixture into a centrifugal machine, carrying out centrifugal separation, and removing the non-adsorbed nano material to obtain a biochar-nano material compound; s7, selecting a natural polymer as a modifier, dissolving according to needs, mixing the biochar-nano material compound and the modifier according to a ratio of 4: 1, fully and uniformly stirring, and adding a proper amount of a cross-linking agent in the stirring process, and S8, drying and crushing, transferring the mixture into a drying oven, and after drying is completed, crushing the mixture into a proper particle size by using a crusher to obtain the biochar-nano material. And finally, screening to remove impurities.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of soil pollution remediation, and in particular to a method for preparing a composite modified biochar soil conditioner. Background Art

[0002] With the acceleration of industrialization, the problem of heavy metal pollution in soil is becoming increasingly serious, seriously affecting the ecological environment and human health. Traditional soil remediation methods such as physical remediation, chemical remediation and biological remediation have their own advantages and disadvantages, making it difficult to achieve efficient, economical and environmentally friendly remediation effects.

[0003] Physical remediation is the use of physical separation remediation, electrokinetics, steam extraction remediation and fixation stabilization remediation technology, biological remediation is the use of microbial or plant metabolic activities to absorb, transform and degrade pollutants in the soil environment, and chemical remediation is the process of dissolving or chemically reacting pollutants to degrade or transform them into low-toxic, low-mobility products. Among them, physical remediation projects are large in scale, high in cost, and limited in depth; although biological remediation has low cost, it has a long cycle and poor results; although chemical remediation has a wide range of applications and high efficiency, unreasonable application will directly aggravate soil degradation and even cause secondary pollution.

[0004] Therefore, there is an urgent need for a new, efficient and sustainable soil heavy metal pollution remediation agent. Summary of the invention

[0005] The technical problem to be solved by the present invention is to overcome the disadvantages of the above-mentioned prior art and provide a method for preparing a composite modified biochar soil conditioner.

[0006] The technical solution adopted to solve the above technical problems is: a method for preparing a composite modified biochar soil conditioner, comprising the following steps:

[0007] S1: Select crop waste (such as rice husks, corn stalks, sawdust), clean it and remove impurities; carbonize the washed waste at a temperature of about 300-600°C and under anaerobic conditions for 2-4 hours to obtain biochar;

[0008] S2: After carbonization is completed, the biochar is cooled and crushed, and sieved to a suitable particle size of about 0.8-1.5 mm;

[0009] S3: Prepare nanomaterials using nano zero-valent iron (nZVI) or nano titanium oxide (TiO 2 );

[0010] S4: weighing the pre-prepared biochar and nanomaterials in a ratio of 3:1;

[0011] S5: Place the biochar and nanomaterials into an ultrasonic cleaning machine, add an appropriate amount of deionized water, and perform ultrasonic treatment (power of about 200 W for 30-60 minutes) to ensure that the nanomaterials are evenly dispersed in the biochar;

[0012] S6: After the ultrasonic treatment, the mixture is transferred to a centrifuge for centrifugal separation to remove the unadsorbed nanomaterials to obtain a biochar-nanomaterial composite;

[0013] S7: Select a natural polymer as a modifier, dissolve it as needed, mix the biochar-nanomaterial composite with the modifier in a ratio of 4:1, and stir well. During the stirring process, a cross-linking agent can be added in an appropriate amount to enhance the stability of the composite;

[0014] S8: Drying and crushing. The mixture is transferred to an oven and the temperature is set to 60-80°C. Drying is performed for 12-24 hours until the water is completely evaporated. After drying, the mixture is crushed into a suitable particle size using a crusher and finally sieved to remove impurities.

[0015] Furthermore, the natural polymer in step S7 is chitosan or polylactic acid.

[0016] Furthermore, the cross-linking agent in S7 is glutaraldehyde.

[0017] Furthermore, the pulverizer in S8 pulverizes the mixture into a particle size of 0.5-1 mm.

[0018] Furthermore, the natural polymer is polylactic acid, and the cross-linking agent is glutaraldehyde. When mixed, the concentration of polylactic acid is 2%, and the added amount of the cross-linking agent is 5% of the mass of the polylactic acid. This ratio can improve the mechanical strength and stability of the composite.

[0019] Furthermore, during the ultrasonic treatment in S5, the ratio of the volume of deionized water to the total mass of the biochar and the nanomaterials is 10:1, and the frequency of the ultrasonic treatment is 40 kHz. The above settings ensure a good dispersion effect and avoid damage to the nanomaterials.

[0020] Furthermore, in the S8 drying step, the temperature of the oven is set to 70° C., the drying time is 18 hours, and during the drying process, the mixture is turned over every 6 hours to ensure uniform evaporation of water, ultimately making the moisture content of the biochar-nanomaterial composite less than 5%.

[0021] Furthermore, the detergent selected in the cleaning step of step S1 is a non-toxic biodegradable cleaning agent, and the formula of the biodegradable cleaning agent includes plant extracts (such as coconut oil, citric acid) and natural surfactants, specifically 30% coconut oil, 10% citric acid, and 60% water. After cleaning, rinse with distilled water twice, and the amount used each time is 3 times the total amount of the cleaning agent to ensure that the residual substances are completely removed.

[0022] Furthermore, the process of the S5 ultrasonic treatment is: after mixing the biochar, nanomaterials and deionized water, place them in an ultrasonic cleaning machine, keep the water temperature at 20-25°C during the treatment process, and immediately transfer them to a centrifuge for subsequent separation after the treatment is completed to avoid aggregation and precipitation of the nanomaterials.

[0023] Furthermore, the temperature used in the S1 carbonization process is 450°C, the carbonization time is 3 hours, and during the carbonization process, a nitrogen protective atmosphere is used to prevent the occurrence of oxidation reactions, thereby increasing the carbon content and pore structure of the biochar, and the nitrogen flow rate used is 2 liters per minute, and the temperature is kept constant for 10 minutes during the heating stage to ensure uniform temperature increase and prevent rapid oxidation of biomass. The specific surface area of ​​the biochar finally obtained reaches 300m 2 / g or above.

[0024] Furthermore, during the S2 screening process, standard sieves are used for grading to ensure the uniformity of the particle size of the final product, thereby improving its dispersibility and effectiveness in the soil. Specifically, the standard sieve apertures used are 1.5 mm and 0.5 mm. First, preliminary screening is performed through a 1.5 mm sieve, and then fine screening is performed through a 0.5 mm sieve to ensure that the particle size distribution of the final product meets the requirements of 0.8-1.5 mm and reduce aggregation between particles.

[0025] The beneficial effects of the present invention are as follows:

[0026] The biochar in the technical solution of the present invention has a rich pore structure and a high specific surface area, which can effectively adsorb heavy metal ions (such as Pb 2+ 、Cd 2+ , Cu 2+ etc.), while nanomaterials (nano zero-valent iron, nano TiO 2 The present invention adopts the composite form of biochar and nanomaterials, makes full use of the physical adsorption characteristics of biochar and the chemical reactivity of nanomaterials, and significantly improves the removal efficiency of heavy metals.

[0027] The invention combines the modification of natural polymers, improves the stability and applicability of the conditioner, and enhances its persistence in the soil.

[0028] The invention adopts a combination of ultrasonic treatment and chemical precipitation to ensure uniform dispersion of nanometer materials and improve the overall performance of the conditioner.

[0029] The application of the biochar of the present invention can increase the pH value of the soil, improve the environment of the acidic soil, and be beneficial to plant growth; the addition of biochar can increase the organic matter content of the soil, improve the fertility and structure of the soil, and the porous structure of the biochar can increase the water retention capacity of the soil, reduce water evaporation, and help plants survive under drought conditions.

[0030] In the soil using the composite conditioner of the present invention, growth indicators such as plant height, leaf number, dry weight, etc. are usually significantly improved, indicating its promoting effect on plant growth and can enhance plant stress resistance: the improved soil environment and nutritional conditions can enhance the resistance of plants to heavy metals and other environmental stresses.

[0031] In addition, by fixing and precipitating heavy metals, the composite conditioner can reduce the bioavailability of heavy metals and reduce potential harm to the environment. Biochar is usually made from agricultural waste or forestry waste, is renewable, and conforms to the concept of sustainable development. Compared with traditional heavy metal remediation methods, the composite conditioner of biochar and nanomaterials can reduce the cost of soil remediation to a certain extent, especially in the treatment of large-scale contaminated soil, and increase crop yields. By improving soil quality and heavy metal removal effects, it can increase crop yields and quality, bringing economic benefits, and the conditioner can be applied to different types of soils (such as sand, clay, loam, etc.) and has strong adaptability. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0033] A method for preparing a composite modified biochar soil conditioner comprises the following steps:

[0034] S1: Select crop waste, clean it and remove impurities; carbonize the cleaned waste at a temperature of about 300-600°C and under anoxic conditions for 2-4 hours to obtain biochar;

[0035] S2: After carbonization is completed, the biochar is cooled and crushed, and sieved to a suitable particle size of about 0.8-1.5 mm;

[0036] S3: Prepare nanomaterials using nano zero-valent iron (nZVI) or nano titanium oxide (TiO 2 );

[0037] S4: weighing the pre-prepared biochar and nanomaterials in a ratio of 3:1;

[0038] S5: Place the biochar and nanomaterials into an ultrasonic cleaning machine, add an appropriate amount of deionized water, and perform ultrasonic treatment (power of about 200 W for 30-60 minutes) to ensure that the nanomaterials are evenly dispersed in the biochar;

[0039] S6: After the ultrasonic treatment, the mixture is transferred to a centrifuge for centrifugal separation to remove the unadsorbed nanomaterials to obtain a biochar-nanomaterial composite;

[0040] S7: Select a natural polymer as a modifier, dissolve it as needed, mix the biochar-nanomaterial composite with the modifier in a ratio of 4:1, and stir well. During the stirring process, a cross-linking agent can be added in an appropriate amount to enhance the stability of the composite;

[0041] S8: Drying and crushing. The mixture is transferred to an oven and the temperature is set to 60-80°C. Drying is performed for 12-24 hours until the water is completely evaporated. After drying, the mixture is crushed into a suitable particle size using a crusher and finally sieved to remove impurities.

[0042] In a preferred embodiment, the natural polymer is polylactic acid and the crosslinking agent is glutaraldehyde. When mixed, the concentration of polylactic acid is 2% and the amount of the crosslinking agent added is 5% of the mass of the polylactic acid. This ratio can improve the mechanical strength and stability of the composite.

[0043] In a preferred embodiment, during the ultrasonic treatment in S5, the ratio of the volume of deionized water to the total mass of the biochar and the nanomaterials is 10:1, and the frequency of the ultrasonic treatment is 40 kHz. The above settings ensure a good dispersion effect and avoid damage to the nanomaterials.

[0044] In a preferred embodiment, in the S8 drying step, the temperature of the oven is set to 70°C, the drying time is 18 hours, and during the drying process, the mixture is turned over every 6 hours to ensure uniform evaporation of water, ultimately making the moisture content of the biochar-nanomaterial composite less than 5%.

[0045] In a preferred embodiment, the detergent used in the cleaning step of step S1 is a non-toxic biodegradable cleaning agent, the formula of the biodegradable cleaning agent includes plant extracts (such as coconut oil, citric acid) and natural surfactants, specifically 30% coconut oil, 10% citric acid, and 60% water. After cleaning, rinse with distilled water twice, and the amount used each time is 3 times the total amount of the cleaning agent to ensure that the residual substances are completely removed.

[0046] In a preferred embodiment, the process of the S5 ultrasonic treatment is: after mixing the biochar, nanomaterials and deionized water, place them in an ultrasonic cleaning machine, keep the water temperature at 20-25°C during the treatment process, and immediately transfer them to a centrifuge for subsequent separation after the treatment is completed to avoid aggregation and precipitation of the nanomaterials.

[0047] In a preferred embodiment, the temperature used in the S1 carbonization process is 450°C, the carbonization time is 3 hours, and during the carbonization process, a nitrogen protective atmosphere is used to prevent the occurrence of oxidation reactions, thereby increasing the carbon content and pore structure of the biochar, and the nitrogen flow rate used is 2 liters per minute, and the temperature is kept constant for 10 minutes during the heating stage to ensure uniform temperature increase and prevent rapid oxidation of biomass. The specific surface area of ​​the biochar finally obtained reaches 300m 2 / g or above.

[0048] In a preferred embodiment, during the S2 screening process, standard sieves are used for grading to ensure the uniformity of the particle size of the final product, thereby improving its dispersibility and effectiveness in the soil. Specifically, the standard sieve apertures used are 1.5 mm and 0.5 mm. First, preliminary screening is performed through a 1.5 mm sieve, and then fine screening is performed through a 0.5 mm sieve to ensure that the particle size distribution of the final product meets the requirements of 0.8-1.5 mm and reduce aggregation between particles.

[0049] Example 1

[0050] Preparation of Rice Husk Biochar and Nano Zero-Valent Iron Composite Soil Conditioner:

[0051] Raw material: rice husk

[0052] Nanomaterials: Nano-Zero-Valent Iron (nZVI)

[0053] Modifier: Chitosan

[0054] step:

[0055] Biochar preparation: Wash the rice husk and remove impurities.

[0056] The rice husk biochar was obtained by carbonization at 500 °C for 3 h under an inert gas environment (nitrogen).

[0057] After carbonization, the mixture is cooled and crushed to a particle size of 1 mm.

[0058] Composite preparation: Weigh 100 g of biochar and 30 g of nZVI and add 500 mL of deionized water.

[0059] Use an ultrasonic cleaner with a power of 200 W for 40 min to ensure that nZVI is evenly dispersed in the biochar.

[0060] Modifier addition: 10 g chitosan was dissolved in 100 mL acidic solution (pH 4) and then added to the biochar-nZVI mixture and stirred well for 30 min.

[0061] 1 mL of cross-linking agent (glutaraldehyde) was added and stirring was continued for 10 minutes.

[0062] Drying and storage: The mixture was transferred to an oven and dried at 60°C for 24 hours.

[0063] Crush to a particle size of 0.5 mm and store.

[0064] Embodiment 2:

[0065] Preparation of corn straw biochar and nano-titanium oxide composite soil conditioner

[0066] Raw material: corn stalks

[0067] Nanomaterials: Nano titanium oxide (TiO2)

[0068] Modifier: Polylactic acid (PLA)

[0069] step:

[0070] Biochar preparation:

[0071] Wash the corn stalks and remove impurities.

[0072] The corn straw biochar was obtained by carbonization at 400 °C for 2 h under an inert gas environment.

[0073] After carbonization, the mixture is cooled and crushed to a particle size of 1 mm.

[0074] Compound preparation:

[0075] Weigh 100 g of biochar and 20 g of TiO2 and add 400 mL of deionized water.

[0076] Use an ultrasonic cleaner with a power of 150 W for 30 min to ensure that the TiO2 is evenly dispersed.

[0077] Modifier addition:

[0078] Dissolve 15 g of polylactic acid in 100 mL of solvent (such as chloroform), then add it to the biochar-TiO2 mixture and stir well for 20 minutes.

[0079] 1.5 mL of cross-linking agent (glutaraldehyde) was added, and stirring was continued for 5 minutes.

[0080] Drying and storage: The mixture was transferred to an oven and dried at 70°C for 18 hours.

[0081] Crush to a particle size of 0.5 mm and store in a sealed container.

[0082] Example 3

[0083] Preparation of sawdust biochar and nano-alumina composite soil conditioner

[0084] Raw materials: sawdust

[0085] Nanomaterials: Nano-alumina (Al 2 O 3 )

[0086] Modifier: Polyvinyl alcohol (PVA)

[0087] step:

[0088] Biochar preparation:

[0089] Wash the sawdust to remove impurities.

[0090] The wood chip biochar was obtained by carbonization at 600 °C for 4 h under an inert gas environment.

[0091] After carbonization, the mixture is cooled and crushed to a particle size of 1 mm.

[0092] Compound preparation:

[0093] Weigh 100g biochar and 25g Al 2 O 3 , add 500mL of deionized water.

[0094] Use an ultrasonic cleaner with a power of 250W for 50 minutes to ensure that Al 2 O 3 Evenly dispersed.

[0095] Modifier addition: Dissolve 20 g of polyvinyl alcohol in 200 mL of deionized water, heat to 70 °C, and keep stirring.

[0096] Biochar-Al 2 O 3 The mixture was added to the PVA solution and stirred thoroughly for 30 minutes.

[0097] Add 2 mL of a cross-linking agent (such as glutaraldehyde) and continue stirring for 10 minutes.

[0098] Drying and storage: The mixture was transferred to an oven and dried at 65°C for 20 hours.

[0099] Crush to a particle size of 0.5 mm and store in a sealed container.

[0100] The conditioning agent prepared in the above embodiment is experimentally tested under laboratory conditions to specifically analyze its removal effect on different heavy metals (such as lead, cadmium, arsenic, copper, etc.).

[0101] Experimental Materials:

[0102] Conditioner: A biochar-nanomaterial composite conditioner prepared using the above method.

[0103] Heavy metal standard solution: lead (Pb 2+ ), cadmium (Cd 2+ ), arsenic (As 3+ ), copper (Cu 2+ ) standard solution.

[0104] Soil samples: Select soil samples contaminated by heavy metals and perform pretreatment (such as drying and crushing).

[0105] Experimental steps:

[0106] Soil Contaminant Preparation:

[0107] The soil samples were treated with heavy metal standard solutions to prepare heavy metal contaminated soils of different concentrations (eg, 100 mg / kg, 200 mg / kg, 500 mg / kg).

[0108] Conditioner Application:

[0109] Different amounts of conditioners (such as 5 g / kg, 10 g / kg, and 20 g / kg) were mixed with heavy metal contaminated soil.

[0110] Cultivation and response:

[0111] The treated soil samples were placed in an incubator, maintained at suitable humidity and temperature (eg, 25° C., 60% humidity), and the incubation time was set to 30 days.

[0112] Sample collection and analysis:

[0113] After the incubation period, samples were taken to analyze the residual concentration of heavy metals in the soil of each group.

[0114] Heavy metals in soil were extracted using acid digestion and quantitatively analyzed using atomic absorption spectrometry (AAS) or inductively coupled plasma mass spectrometry (ICP-MS).

[0115] Data Analysis:

[0116] Calculation of heavy metal removal rate:

[0117] Calculate the removal rate of each heavy metal in each group of soil:

[0118] Where C0 is the initial heavy metal concentration, and Cf is the heavy metal concentration after treatment.

[0119] Experimental results record:

[0120] The removal effects of different amounts of conditioners on various heavy metals were recorded, and the data table 1 is as follows:

[0121]

[0122] Experimental data analysis:

[0123] It can be seen from the data table that with the increase in the amount of conditioning agent, the removal rate of heavy metals is significantly improved, especially the removal effect of heavy metals such as lead, cadmium, and copper reached more than 90% at a dosage of 20g / kg.

[0124] The removal effect of cadmium was also good, indicating that the conditioner had good adsorption capacity for different types of heavy metals. The removal rate of arsenic was relatively low, which may be related to its chemical form and competition with other ions present in the soil.

[0125] Example 4

[0126] Further real-world soil was collected for analysis. The soil was collected from an industrial site in Xuezhuang Village, Jiaxiang County, Jining City, Shandong Province, which was contaminated with heavy metals Pb and Cd. The soil was naturally air-dried and then passed through a 2 mm sieve. The basic physical and chemical properties of the soil are shown in Table 2:

[0127]

[0128] The conditioning agents CS1, CS2 and CS3 prepared in the above-mentioned Examples 1, 2 and 3 were applied to the contaminated soil according to a certain proportion of the dry weight of the soil, mixed thoroughly, and allowed to stand for 14 days for curing. The restoration effect and the fertility properties of the soil after restoration were compared. For comparison, the contaminated soil was restored by using the general soil restoration agent PT available on the market under the same restoration experimental conditions as the restoration conditioning agent of the present invention. The restoration effect comparison is as follows:

[0129] Table 3 shows:

[0130] Conditioner Type Soil pH after restoration Pb leaching concentration mg / L Cd leaching concentration mg / L CS1 7.42 0.0165 0.0025 CS2 7.49 0.0206 0.0032 CS3 7.71 0.0204 0.0018 PT 7.2 0.1698 0.0148

[0131] Soil properties after restoration: Table 4

[0132]

[0133] Through specific experimental analysis, it can be known that the biochar soil conditioner of the embodiment of the present invention can effectively adsorb heavy metal ions in the soil, and nanomaterials can enhance the removal effect of heavy metals through chemical reactions. By combining biochar and nanomaterials, a synergistic effect can be exerted to improve the overall removal efficiency, reduce the limitations of a single material, and significantly improve the removal efficiency of heavy metals.

[0134] The application of the soil conditioner of the present invention can increase the pH value of the soil, improve the environment of the acidic soil, and be beneficial to plant growth; the addition of biochar can increase the organic matter content of the soil, improve the fertility and structure of the soil, and the porous structure of the biochar can increase the water retention capacity of the soil, reduce water evaporation, and help plants survive under drought conditions.

[0135] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a composite modified biochar soil conditioner, characterized in that: The following steps are involved: S1: Select crop waste (such as rice husks, corn stalks, sawdust), clean it and remove impurities; carbonize the washed waste at a temperature of about 300-600°C and under anaerobic conditions for 2-4 hours to obtain biochar; S2: After carbonization is completed, the biochar is cooled and crushed, and sieved to a suitable particle size of about 0.8-1.5 mm; S3: preparing nanomaterials, using nano zero-valent iron (nZVI) or nano titanium oxide (TiO2); S4: weighing the pre-prepared biochar and nanomaterials in a ratio of 3:1; S5: Place the biochar and nanomaterials into an ultrasonic cleaning machine, add an appropriate amount of deionized water, and perform ultrasonic treatment (power of about 200 W for 30-60 minutes) to ensure that the nanomaterials are evenly dispersed in the biochar; S6: After the ultrasonic treatment, the mixture is transferred to a centrifuge for centrifugal separation to remove the unadsorbed nanomaterials to obtain a biochar-nanomaterial composite; S7: Select a natural polymer as a modifier, dissolve it as needed, mix the biochar-nanomaterial composite with the modifier in a ratio of 4:1, and stir well. During the stirring process, a cross-linking agent can be added in an appropriate amount to enhance the stability of the composite; S8: Drying and crushing. The mixture is transferred to an oven and the temperature is set to 60-80°C. Drying is performed for 12-24 hours until the water is completely evaporated. After drying, the mixture is crushed into a suitable particle size using a crusher and finally sieved to remove impurities.

2. The method for preparing a composite modified biochar soil conditioner according to claim 1, characterized in that: The natural polymer in step S7 is chitosan or polylactic acid.

3. The method for preparing a composite modified biochar soil conditioner according to claim 1, characterized in that: The cross-linking agent in S7 is glutaraldehyde.

4. The method for preparing a composite modified biochar soil conditioner according to claim 1, characterized in that: The pulverizer in S8 pulverizes the mixture into a particle size of 0.5-1 mm.

5. The method for preparing a composite modified biochar soil conditioner according to claim 2, characterized in that: The natural polymer is polylactic acid, and the cross-linking agent is glutaraldehyde. When mixed, the concentration of polylactic acid is 2%, and the added amount of the cross-linking agent is 5% of the mass of the polylactic acid. This ratio can improve the mechanical strength and stability of the composite.

6. The method for preparing a composite modified biochar soil conditioner according to claim 1, characterized in that: During the ultrasonic treatment in S5, the ratio of the volume of deionized water to the total mass of the biochar and the nanomaterials is 10:1, and the frequency of the ultrasonic treatment is 40 kHz. The above settings ensure a good dispersion effect and avoid damage to the nanomaterials.

7. The method for preparing a composite modified biochar soil conditioner according to claim 1, characterized in that: In the S8 drying step, the temperature of the oven is set to 70° C., the drying time is 18 hours, and during the drying process, the mixture is turned over every 6 hours to ensure uniform evaporation of water, and finally the moisture content of the biochar-nanomaterial composite is less than 5%.

8. The method for preparing a composite modified biochar soil conditioner according to claim 1, characterized in that: The detergent selected in the cleaning step of step S1 is a non-toxic biodegradable cleaning agent. The formula of the biodegradable cleaning agent includes plant extracts (such as coconut oil, citric acid) and natural surfactants, specifically 30% coconut oil, 10% citric acid, and 60% water. After cleaning, rinse twice with distilled water, and the amount used each time is 3 times the total amount of the cleaning agent to ensure that the residual substances are completely removed.

9. The method for preparing a composite modified biochar soil conditioner according to claim 1, characterized in that: The process of the S5 ultrasonic treatment is: after mixing the biochar, nanomaterials and deionized water, place them in an ultrasonic cleaning machine, keep the water temperature at 20-25°C during the treatment process, and immediately transfer them to a centrifuge for subsequent separation after the treatment is completed to avoid aggregation and precipitation of the nanomaterials.

10. The method for preparing a composite modified biochar soil conditioner according to claim 1, characterized in that: The temperature used in the S1 carbonization process is 450°C, the carbonization time is 3 hours, and during the carbonization process, a nitrogen protective atmosphere is used to prevent the occurrence of oxidation reactions, thereby increasing the carbon content and pore structure of the biochar. The nitrogen flow rate used is 2 liters per minute, and the temperature is kept constant for 10 minutes during the heating stage to ensure uniform temperature increase and prevent rapid oxidation of biomass. The specific surface area of ​​the final biochar reaches 300m 2 / g or above.

11. The method for preparing a composite modified biochar soil conditioner according to claim 1, characterized in that: During the S2 screening process, standard sieves are used for grading to ensure the uniformity of the particle size of the final product, thereby improving its dispersibility and effectiveness in the soil. Specifically, the standard sieve apertures used are 1.5 mm and 0.5 mm. First, preliminary screening is performed through a 1.5 mm sieve, and then fine screening is performed through a 0.5 mm sieve to ensure that the particle size distribution of the final product meets the requirements of 0.8-1.5 mm and reduce the aggregation phenomenon between particles.